2016
DOI: 10.1073/pnas.1603486113
|View full text |Cite
|
Sign up to set email alerts
|

Mutant cycle analysis with modified saxitoxins reveals specific interactions critical to attaining high-affinity inhibition of hNa V 1.7

Abstract: Improper function of voltage-gated sodium channels (Na V s), obligatory membrane proteins for bioelectrical signaling, has been linked to a number of human pathologies. Small-molecule agents that target Na V s hold considerable promise for treatment of chronic disease. Absent a comprehensive understanding of channel structure, the challenge of designing selective agents to modulate the activity of Na V subtypes is formidable. We have endeavored to gain insight into the 3D architecture of the outer vestibule of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 48 publications
1
57
0
Order By: Relevance
“…To our knowledge, an analogous study has not been reported to date for a Nav channel binding to an ICK peptide. Parsons and Du Bois synthesized maleimide crosslinkers based on smallmolecule Nav pore-blocker saxitoxin; however, identification of the sites of interaction in their subsequent work was indirect, and based on mutagenesis (Parsons and Du Bois, 2013;Thomas-Tran and Du Bois, 2016). Whilst elegant work by Catterall and colleagues determined photocrossinglinking sites for a scorpion toxin using sequence-specific antibodies (Tejedor and Catterall, 1988), the closest comparable example of identification of a photocrosslinking site by mass spectrometry was reported for a simple sevoflurane analog on a voltage-gated potassium channel Kv1.2 (Woll et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, an analogous study has not been reported to date for a Nav channel binding to an ICK peptide. Parsons and Du Bois synthesized maleimide crosslinkers based on smallmolecule Nav pore-blocker saxitoxin; however, identification of the sites of interaction in their subsequent work was indirect, and based on mutagenesis (Parsons and Du Bois, 2013;Thomas-Tran and Du Bois, 2016). Whilst elegant work by Catterall and colleagues determined photocrossinglinking sites for a scorpion toxin using sequence-specific antibodies (Tejedor and Catterall, 1988), the closest comparable example of identification of a photocrosslinking site by mass spectrometry was reported for a simple sevoflurane analog on a voltage-gated potassium channel Kv1.2 (Woll et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it should be noted that most secondary metabolites produced via NRPS/PKS are modular compounds, and it is currently recognized that variability in one or more substituents leads to different target specificity. For example, the affinity for genetic variants of the same ion channel differs across saxitoxin analogs 31 , whereas the specificity for serine proteases with trypsin- and thrombin-like activity differs among aeruginosins 32 . Thus, the grouping of biosynthetic gene clusters according to the chemical structure of the secondary metabolite likely reflects the bioactivity of the metabolite rather than its specific chemical structure.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the carbamoyl group at C13 in STX (1) interacts with Gly1407 and Thr1409 in domain III, the two guanidines interact with Glu364 in domain I and Glu930 in domain II, and the geminal diol interacts with Asp1701 in domain IV. Interestingly, residues 1409 and 1410, located in the P2 loop of domain III in Na V 1.7, were mutated to Thr and Ile from Met and Asp, respectively, which may explain why STX (1) has a weaker affinity for Na V 1.7 compared with other subtypes (Met1409 and Asp1410 are conserved in the other subtypes of TTX-s) [46,47].…”
Section: Voltage-gated Sodium Channel Isoformsmentioning
confidence: 99%
“…Synthetic studies of STX (1) and its analogs have been extensive, and several total syntheses have been achieved [52][53][54][55][56][57][58][59][60][61], as recently reviewed by Du Bois [62]. Approaches for developing of subtype-selective modulators based on the STX structure have also been explored [25,47,[63][64][65]. However, in this review, we focus on recent synthetic work related to ZTX (8).…”
Section: Scope Of This Reviewmentioning
confidence: 99%